Evolution and degradation of flat‐top mesas in the hyper‐arid Negev, Israel revealed from 10Be cosmogenic nuclides. Issue 12 (1st April 2014) - Boroda, Ronen; Matmon, Ari; Amit, Rivka; Haviv, Itai; Arnold, Maurice; Aumaître, Georges; Bourlès, Didier L.; Keddadouche, Karim; Eyal, Yehuda; Enzel, Yehouda
ABSTRACT Mesas are ubiquitous landforms in arid and semiarid regions and are often characterized by horizontal stratified erodible rocks capped by more resistant strata. The accepted conceptual model for mesa evolution and degradation considers reduction in the width of the mesa flat‐top plateau due to cliff retreat but ignores possible denudation of the mesa flat‐top and the rates and mechanism of erosion. In this study we examine mesas in the northeastern hyperarid Negev Desert where they appear in various sizes and morphologies and represent different stages of mesa evolution. The variety of mesas within a single climatic zone allows examination of the process of mesa evolution through time. Two of the four sites examined are characterized by a relatively wide (200–230 m) flat‐top and a thick caprock whereas the other two are characterized by a much narrower remnant flat‐top (several meters) and thinner caprock. We use the concentration of the cosmogenic nuclide 10Be for: (a) determining the chronology of the various geomorphic features associated with the mesa; and (b) understanding geomorphic processes forming the mesa. The 10Be data, combined with field observations, suggest a correlation between the width of flat‐top mesa and the denudation and cliff retreat rates. Our results demonstrate that: (a) cliff retreat rates decrease with decreasing width of the flat‐top mesa; (b) vertical denudation rates increase with decreasing width of the flat‐top mesa below a critical value ( 60 m, for the Negev Desert); (c) the reduction in the width of the flat‐top mesa is driven mainly by cliff retreat accompanied by extremely slow vertical denudation rate which can persist for a very long time (>106 Ma); and (d) when the width of the mesa decreases below a certain threshold, its rate of denudation increases dramatically and mesa degradation is completed in a short time. Copyright © 2014 John Wiley & Sons, Ltd.